Altered expression of glycan patterns and glycan-related genes in the medial prefrontal cortex of the valproic acid rat model of autism - Liu, Yingxun; Di, Yuanyuan; Zheng, Qi; Qian, Zhaoqiang; Fan, Juan; Ren, Wei; Wei, Zhaoming; Tian, Yingfang (Frontiers in Cellular Neuroscience, 2022)
Autism spectrum disorders (ASD) represent a group of neurodevelopmental defects characterized by social deficits and repetitive behaviors. Alteration in Glycosylation patterns could influence the nervous system development and contribute to the molecular mechanism of ASD. Interaction of environmental factors with susceptible genes may affect expressions of glycosylation-related genes and thus result in abnormal glycosylation patterns. Here, we used an environmental factor-induced model of autism by a single intraperitoneal injection of 400 mg/kg valproic acid (VPA) to female rats at day 12.5 post-conception. Following confirmation of reduced sociability and increased self-grooming behaviors in VPA-treated offspring, we analyzed the alterations in the expression profile of glycan patterns and glycan-related genes by lectin microarrays and RNA-seq, respectively. Lectin microarrays detected 14 significantly regulated lectins in VPA rats, with an up-regulation of high-mannose with antennary and down-regulation of Siaα2-3 Gal/GalNAc. Based on the KEGG and CAZy resources, we assembled a comprehensive list of 961 glycan-related genes to focus our analysis on specific genes. Of those, transcription results revealed that there were 107 differentially expressed glycan-related genes (DEGGs) after VPA treatment. Functional analysis of DEGGs encoding anabolic enzymes revealed that the process trimming to form core structure and glycan extension from core structure primarily changed, which is consistent with the changes in glycan patterns. In addition, the DEGGs encoding glycoconjugates were mainly related to extracellular matrix and axon guidance. This study provides insights into the underlying molecular mechanism of aberrant glycosylation after prenatal VPA exposure, which may serve as potential biomarkers for the autism diagnosis.